β-hydroxybutyrate administration improves liver injury and metabolic abnormality in postnatal growth retardation piglets - Wang, Chengming; Wang, Nan; Deng, Yuankun; Zha, Andong; Li, Junyao; Tan, Bie; Qi, Ming; Wang, Jing; Yin, Yulong (Frontiers in Veterinary Science, 2023)
Abnormal hepatic energy metabolism limits the growth and development of piglets.We hypothesized that β-hydroxybutyrate (BHB) might improve the growth performance of piglets by maintaining hepatic caloric homeostasis. A total of 30 litters of newborn piglets were tracked, and 30 postnatal growth retardation (PGR) piglets and 40 healthy piglets were selected to treat with normal saline with or without BHB (25mg/kg/ days) at 7-d-old. At the age of 42 days, 8 piglets in each group were sacrificed, and serum and liver were collected. Compared with the healthy-control group piglets, PGR piglets showed lower body weight (BW) and liver weight (P < 0.05), and exhibited liver injury and higher inflammatory response. The contents of serum and hepatic BHB were lower (P < 0.05), and gene expression related to hepatic ketone body production were down-regulated in PGR piglets (P < 0.05). While BHB treatment increased BW and serum BHB levels, but decreased hepatic BHB levels in PGR piglets (P < 0.05). BHB alleviated the liver injury by inhibiting the apoptosis and inflammation in liver of PGR piglets (P < 0.05). Compared with the healthy-control group piglets, liver glycogen content and serum triglyceride level of PGR piglets were increased (P < 0.05), liver gluconeogenesis gene and lipogenesis gene expression were increased (P < 0.05), and liver NAD + level was decreased (P < 0.05). BHB supplementation increased the ATP levels in serum and liver (P < 0.05), whereas decreased the serum glucose, cholesterol, triglyceride and high-density lipoprotein cholesterol levels and glucose and lipid metabolism in liver of PGR piglets (P < 0.05). Therefore, BHB treatment might alleviate the liver injury and inflammation, and improve hepatic energy metabolism by regulating glucose and lipid metabolism, thereby improving the growth performance of PGR piglets.